2012
DOI: 10.1111/j.1468-3148.2012.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multisensory Environments on Stereotyped Behaviours Assessed as Maintained by Automatic Reinforcement

Abstract: The results are consistent with the hypothesis that reductions in stereotyped behaviour observed in MSEs are due to the increased levels of specific sensory stimulation provided by such environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
20
0
3
Order By: Relevance
“…Phenomenologically, tics and rodent stereotypies have a number of characteristics in common. Like tics, spontaneous stereotypies in animals can be interrupted by distractors (Hill et al, 2012; Mason and Newsom, 1990; Oakley et al, 2015). Both tics and animal stereotypies can be precipitated by contextual triggers and particular psychological states, such as high or low sensory stimulation, stress, anxiety, frustration, and fatigue (Conelea and Woods, 2008; Godar and Bortolato, 2016; Kurlan, 2010; Leckman, 2002; Mason, 1991).…”
Section: Studying Tic-like Movements Using a Phenomenological Approachmentioning
confidence: 99%
“…Phenomenologically, tics and rodent stereotypies have a number of characteristics in common. Like tics, spontaneous stereotypies in animals can be interrupted by distractors (Hill et al, 2012; Mason and Newsom, 1990; Oakley et al, 2015). Both tics and animal stereotypies can be precipitated by contextual triggers and particular psychological states, such as high or low sensory stimulation, stress, anxiety, frustration, and fatigue (Conelea and Woods, 2008; Godar and Bortolato, 2016; Kurlan, 2010; Leckman, 2002; Mason, 1991).…”
Section: Studying Tic-like Movements Using a Phenomenological Approachmentioning
confidence: 99%
“…Although MSEs are widely used with autistic pupils, there is a clear need for further evidence-based research to support their use ( Botts et al, 2008 ; Cameron et al, 2019 ; Lotan & Gold, 2009 ). Previous work has demonstrated that the way MSEs are used can affect outcomes ( Fava & Strauss, 2010 ; Glenn et al, 1996 ; Hill et al, 2012 ). For example, Fava and Strauss (2010) reported a reduction in stereotyped behaviours in their autistic and intellectual disabled (ID) adult participants when the MSE session was unstructured compared to when it was structured.…”
Section: Introductionmentioning
confidence: 99%
“…Consiste no uso de equipamentos específicos, no interior de uma sala, que permite a exploração controlada dos diversos sentidos: tátil, visual, olfativo, auditivo, vestibular e propriocetivo 2 . Estes equipamentos podem promover a estimulação contingente, na qual o utilizador desenvolve um comportamento que irá desencadear uma resposta do equipamento, ou não contingente, em que este apenas recebe um estímulo e a sua resposta não apresenta qualquer alteração no ambiente 11 .…”
Section: Introductionunclassified
“…As sessões realizadas nessas salas podem ser individuais ou de grupo, e o papel dos técnicos deve ser o de permitir e encorajar a interação dos participantes com o equipamento destinado à estimulação 2,11 .…”
Section: Introductionunclassified
See 1 more Smart Citation